Percy Jackson: The Demigod Files (Percy Jackson & the Olympians) - Rick Riordan (LONDON PENGUIN, 2009)
In these top-secret files, Rick Riordan, Camp Half-Blood's senior scribe, gives you an inside look at the world of demigods that NO regular human child is allowed to see. These highly classified archives include three of Percy Jackson's most perilous adventures, a Spotter's Guide to Monsters, a Who's Who in Greek Mythology, Percy's Summer Camp report and much more. So, if you're armed with this book, you'll have everything You need to know to keep you alive in your training, your own adventures have just begun...